A Real-World Analysis of Patients with Triple Class Exposed Multiple Myeloma in Italy: Epidemiology Estimates, Treatment Pattern and Economic Burden - Perrone, Valentina; Mazzoni, Stefania; Cappuccilli, Maria; Di Virgilio, Roberto; Degli Esposti, Luca (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
OBJECTIVES: This research aimed to provide updated epidemiological estimates of multiple myeloma (MM) in Italy and to characterize the clinical journey, treatment patterns, and economic burden focusing specifically on the subset of patients who have been exposed to all three major therapeutic classes: proteasome inhibitors, immunomodulatory drugs, and antiCD38 monoclonal antibodies (triple-class exposed, TCE).METHODS: A retrospective analysis was conducted using Italian healthcare administrative databases covering 12 million individuals. The research included (i) an epidemiological analysis of MM prevalence and incidence, and (ii) a longitudinal analysis of TCE patients identified between January 2017 and June 2023. Inclusion criteria required exposure to the three major MM drug classes. Healthcare resource utilization (HCRU) and direct costs from the Italian National Health Service perspective were assessed at one-year follow-up.RESULTS: As of August 2022, MM incidence was 9/100,000 and prevalence 40.9/100,000; TCE prevalence was estimated at 4.1/100,000, projecting to 2,557 TCE patients in Italy. From 6,102 MM patients, 894 were identified as TCE; 887 had sufficient follow-up for inclusion. TCE patients had a mean age of 67 years and a mild comorbidity burden (Charlson Index = 0.7). Among 309 recent TCE cases (2022–2023), 35.6% became TCE in first-line therapy and 46.5% in second-line. HCRU analysis (n=461) showed high service use, with annual per-patient costs averaging €119,899—88% attributable to MM-related drugs.CONCLUSIONS: This real-world analysis highlights a growing population of TCE MM patients in Italy, with increasing exposure to combination therapies earlier in treatment. The findings underscore the substantial clinical and economic burden posed by this population, reinforcing the need for novel therapeutic options to improve outcomes and manage costs within the healthcare system.